Do communities really have a say? The implementation of public participation in the liquor regulatory process: A case study of uMgungundlovu District - Colborne, Meryl-lynne (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPA)--Stellenbosch University, 2021.